It Takes More than a Mandate: Factors that Contribute to Increased Rates of Article Deposit to an Institutional Repository - Deborah Barreau; Hui Zhang (Journal of Librarianship and Scholarly Communication, 2015)
INTRODUCTION Many institutions have open access (OA) policies that require faculty members to deposit their articles in an institutional repository (IR). A clear motivation is that a policy will result in increased self-archiving. The purpose of this longitudinal study is to compare the impact of a campus-wide OA policy and mediated solicitation of author manuscripts, using quantitative analysis to determine the rate of article deposits over time. METHODS Metadata for faculty articles published by authors at Oregon State University between 2011 and 2014 was produced by integrating citation metadata from a bibliographic database and the IR. Author names, affiliations, and other metadata were parsed and matched to compare rates of deposit for three separate time periods relating to different OA promotional strategies. RESULTS Direct solicitation of author manuscripts is more successful in facilitating OA than an OA policy—by number of articles deposited as well as the number of unique authors participating. Author affiliation and research areas also have an impact on faculty participation in OA. DISCUSSION Outreach to colleges and departments has had a positive effect on rate of deposit for those communities of scholars. Additionally, disciplinary practice may have more influence on its members’ participation in OA. CONCLUSION Until more federal policies require open access to articles funded by grants, or institutional policies are in place that require article deposit for promotion and tenure, policies will only be as effective as the library mediated processes that are put in place to identify and solicit articles from faculty.